Cochrane Database of Systematic Reviews 2016
DOI: 10.1002/14651858.cd012055
|View full text |Cite
|
Sign up to set email alerts
|

Alternative agents versus prophylactic platelet transfusion for preventing bleeding in patients with thrombocytopenia due to chronic bone marrow failure: a network meta-analysis and systematic review

Abstract: This is the protocol for a review and there is no abstract. The objectives are as follows: To compare the relative efficacy of different treatments for thrombocytopenia (artificial platelet substitutes, platelet-poor plasma, fibrinogen, rFVIIa, rFXIII, thrombopoietin mimetics, antifibrinolytic drugs or platelet transfusions) in patients with chronic bone marrow failure and to derive a hierarchy of potential alternate treatments to platelet transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The optimum platelet count threshold for transfusion is significantly variable depending on the underlying etiology, clinical practice setting, and geographic location, which needs further evaluation (72). At present, there is a lack of evidence to replace platelet transfusions with the newer platelet substitutes, such as artificial platelets, recombinant interleukin-6 or-11, and thrombopoietin mimetics (73).…”
Section: Knowledge Gap and Future Directionsmentioning
confidence: 99%
“…The optimum platelet count threshold for transfusion is significantly variable depending on the underlying etiology, clinical practice setting, and geographic location, which needs further evaluation (72). At present, there is a lack of evidence to replace platelet transfusions with the newer platelet substitutes, such as artificial platelets, recombinant interleukin-6 or-11, and thrombopoietin mimetics (73).…”
Section: Knowledge Gap and Future Directionsmentioning
confidence: 99%
“…If subgroup data for haematological participants were not provided (after contacting the authors of the trial), we excluded trials if less than 80% of participants had a haematological disorder. We excluded any participants that were not treated with intensive chemotherapy or a stem cell transplant as these participants are the focus of another review (Desborough 2016). We included participants with non-malignant haematological disorders (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…We also excluded people treated with non-intensive chemotherapy (such as azacitidine, decitabine and lenalidomide) because the degree of thrombocytopenia is much less profound with a lower risk of bleeding. Trials in people with chronic bone marrow failure using these agents are reported in another review (Desborough 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations